PENINGKATAN KETERAMPILAN MENULIS CERPEN PADA PEMBELAJARAN BERDIFERENSIASI SISWA KELAS XI SMAN 1 TAKALAR: Improving Short Story Writing Skills in Differentiated Learning Class Xi Students at Sman 1 Takalar - Muh. Rafly Rahmaluddin; Usman; Abd. Rahim (Journal of Applied Linguistics and Literature, 2026)
This study aims to describe the implementation of short story writing in differentiated learning for 11th-grade students of SMA Negeri 1 Takalar and to identify and analyze the improvement of short story writing skills within this learning approach. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of two sessions: Cycle 1 Session 1, Cycle 1 Session 2, Cycle 2 Session 1, and Cycle 2 Session 2, which included planning, action implementation, observation, and reflection stages. The research data comprised the process of short story writing learning, the outcomes of short story writing learning, and interview results, analyzed using qualitative descriptive techniques for process data and quantitative descriptive techniques for outcome data. The research subjects consisted of one teacher and 36 students from class XI.1 Archimedes SMA Negeri 1 Takalar. Data collection was carried out through observations, interviews, and assessments in the form of short story writing tasks. The results indicated an increase in teacher and student activities from Cycle 1 to Cycle 2. The number of students capable of writing short stories increased from 4 students (11.1%) in Cycle 1 Session 1 to 8 students (22.2%) in Cycle 1 Session 2, further increasing to 19 students (52.8%) in Cycle 2 Session 1, and ultimately reaching 34 students (94.4%) in Cycle 2 Session 2. Thus, this study demonstrates an improvement in short story writing skills in differentiated learning among students of class XI.1 Archimedes SMA Negeri 1 Takalar